Penggunaan Gambar Berseri sebagai Media untuk Meningkatkan Ketrampilan Menulis Teks Prosedur pada Siswa S1 Keperawatan STIKes Patria Husada Blitar - Wahyu Wibisono; Lely Indah Kurnia; Fitria Nur Hamidah; Muhammad Muchlisin (STIKes Patria Husada Blitar, 2016)
English become the most important things in facing the issue of Asean Economic Community (AEC) especially in the health sector since English is one of the international language use in asean. So, preparing medical employees with English become a great issue to be solved. This study was intended to apply picture Series as the media to improve students writing skill. The research design used was collaborative Classroom Action Research. The collaboration was done with three English teachers in STIKes Patria Husada Blitar. This Classroom Action Research was implemented in one cycle only which involved four stages namely planning, implementation, observation, and reflection. The researcher gained the data in the form of students’ involvement during teaching learning activity and the writing product. To get those data, the researcher used several instruments; those were students writing product and field notes. The finding of this study showed that by using picture series as the media, the students could write procedure text much better than they were taught using traditional grammar translation method. In terms of the students’ individual writing product, in preliminary study, the number of students who passed the minimum passing grade (64) was only 2 students (9.1%). On the other hand, in Cycle 1, all of the 22 students (100%) could pass the minimum passing grade (64). The improvement of students’ writing skill was due to the use of picture series as the media in teaching writing which consisted of several activities for the students so that they were enthusiastic in joining the class. In addition, it was suggested for the lecturers and/ or teacher to apply and modify this technique in their classes.